Implementation of Tracking System Based on JT701 Smart Lock Technology on Goods Delivery Service Vehicles - Sundawa, Bakti Viyata; Amalia; Batubara, Febrin Aulia; Nasution, Tuti Adi Tama; Pardede, Morlan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The goods delivery service industry has emerged as a strategic business both during and after the pandemic. The shift towards online shopping, which became a norm during the pandemic, let’s continue post-pandemic, making it a promising sector for companies involved in goods delivery. However, the industry faces challenges, particularly related to security during shipment. One common issue is the inability to track vehicle positions, leading to unauthorized loading and unloading activities at incorrect locations, causing losses for business owners. Conventional mechanical locks are vulnerable to theft, duplication, key loss, and vandalism, making them inadequate for securing cargo. To address these issues, Smart Lock technology has been developed, offering enhanced security through modern, integrated features. This technology eliminates the need for physical keys, reducing the risk of loss, and allows for remote access management. Additionally, it enables cargo owners to monitor the vehicle's position and control the lock remotely. Given these advancements, there is a need to explore Tracking Systems for delivery vehicles, incorporating automatic locks controlled via Internet of Things (IoT) technology. Based on the measurement, the tracking system tool testing was carried out at 5 different locations. The distances are 2.9 km, 6.4 km, 3 km, 7.1 km, 4.7 km from campus. The GPS signal is sent to the cloud server Cloud of Jointech. Data transmission uses the GSM network. There is a delay difference of 2-3 seconds from the GPS time signal compared to the time data displayed on the website. The data provided from the GPS signal is updated every 20 seconds. Based on the 5 test locations that have been set, the on/off lock test has been successfully carried out.